2020
DOI: 10.1038/s41598-020-60294-x
|View full text |Cite|
|
Sign up to set email alerts
|

Supervised deep learning for real-time quality monitoring of laser welding with X-ray radiographic guidance

Abstract: Laser welding is a key technology for many industrial applications. However, its online quality monitoring is an open issue due to the highly complex nature of the process. this work aims at enriching existing approaches in this field. We propose a method for real-time detection of process instabilities that can lead to defects. Hard X-ray radiography is used for the ground truth observations of the sub-surface events that are critical for the quality. A deep artificial neural network is applied to reveal the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…WPT spectrograms, formed as the relative energies of the frequency bands, provide simplified time‐frequency representations of the original signals (ie including a lower number of elements and, at the same time, conserving the features of the signal evolution). In the works of Shevchik et al [15, 17, 18], it was shown that such representation of the input data allows reducing the training sets, still providing a high classification accuracy. In the present contribution, these previously reported results were proved, while feeding the raw signals to both algorithms from the training set and showing lower classification accuracy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…WPT spectrograms, formed as the relative energies of the frequency bands, provide simplified time‐frequency representations of the original signals (ie including a lower number of elements and, at the same time, conserving the features of the signal evolution). In the works of Shevchik et al [15, 17, 18], it was shown that such representation of the input data allows reducing the training sets, still providing a high classification accuracy. In the present contribution, these previously reported results were proved, while feeding the raw signals to both algorithms from the training set and showing lower classification accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…Laser‐induced AE is a well‐known phenomenon [7, 13] and the modulations of AE are strongly dependent from the chemical composition, mechanical, and optical properties of the tissues that are exposed to laser irradiation [7, 13]. The same approach has been well established in industrial applications such as laser welding and additive manufacturing [15–19]. Based on these experiences, we believe that this approach will potentially provide information about the ablated zone in biomedical applications as well.…”
Section: Introductionmentioning
confidence: 96%
“…For this reason, the full setup depicted in Fig. 2 This unit is based on our previous work [13], where the AE and OE signals from the PZ were used to identify quality critic momentary events. In this contribution, the output of the classifier is made up of labels that correspond to predefined welding qualities in terms of penetration depth and pore content.…”
Section: B Feedback Networkmentioning
confidence: 99%
“…Consequently, it is difficult to provide an effective feedback from the process to the control system, since it requires the correlation of the surface measurements with the sub-surface events (e.g., pore formation), which is not a trivial task [12]. Nevertheless, some pilot works in LW monitoring report successes in identifying quality critic momentary events from the corresponding AE and OE signals from the processed zone [13], [14]. The present study starts from the aforementioned preliminary results of process monitoring and focuses on the use of Reinforcement Learning (RL) towards keyhole LW closedloop control.…”
Section: Introductionmentioning
confidence: 99%
“…Bacioiu et al [ 18 , 19 ] used CNN models to detect defects in tungsten inert gas welding. Shevchik et al [ 20 ] proposed a method for real-time detection of laser welding instabilities by the application of CNN.…”
Section: Introductionmentioning
confidence: 99%